2020
DOI: 10.20944/preprints202012.0433.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Seasonal and Drought Conditions Effect on Satellite-based Precipitation Data Accuracy over Different Climatic Conditions

Abstract: The Tropical Rainfall Measuring Mission (TRMM) and then Global Precipitation Mission (GPM) are the most important and widely used data sources in the forecasting of drought, flood, and water resources management. However, since this sensor’s data is primarily used for tropical regions, it is necessary to evaluate the accuracy for optimal use of the data across varying climatic and physiographic conditions. In this study, the accuracy of the satellite data for a span of 17 years (2000-2017) for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Some recent examples from the countries adjacent to Afghanistan are highly relevant. Salehnia et al [ 30 ], Zarei et al [ 31 ] and Qureshi et al [ 32 ] examined the ability of SPI or RDI for assessing historical droughts at basin or provincial or national scales of Iran over decades. Al-Mamun et al [ 33 ] identified meteorological drought prone areas in Bangladesh by using monthly precipitation data to generate SPI time series for 35 meteorological stations in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent examples from the countries adjacent to Afghanistan are highly relevant. Salehnia et al [ 30 ], Zarei et al [ 31 ] and Qureshi et al [ 32 ] examined the ability of SPI or RDI for assessing historical droughts at basin or provincial or national scales of Iran over decades. Al-Mamun et al [ 33 ] identified meteorological drought prone areas in Bangladesh by using monthly precipitation data to generate SPI time series for 35 meteorological stations in the country.…”
Section: Introductionmentioning
confidence: 99%